Surgical management of benign peripheral nerve tumors (Faculty of Medicine Universitas Indonesia, 2008)
Peripheral nerve tumors are rare lesions that can arise anywhere in the body and hence have a myriad of wide differential diagnosis. They commonly present as a non-specific mass which is diagnosed as a peripheral nerve tumor at surgery. While these tumors may initially be referred to a wide variety of surgeons, early recognition of the nature of the lesion and appropriate surgical treatment by an expert peripheral nerve surgeon is essential in order to minimize post-operative neurological deficits. The objective of this article is to provide a general management scheme for the most common setting of benign peripheral nerve tumors. (Med J Indones 2008; 17: 163-8)